A method for oxidizing thioether

CN114436917BActive Publication Date: 2025-02-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202011197924.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-10-30
Publication Date
2025-02-11
Estimated Expiration
2040-10-30

AI Technical Summary

Technical Problem

The current dimethyl sulfoxide production cost is relatively high, mainly because the price and amount of oxidants in the peroxide oxidation method are high, which limits the application scope of this method.

Method used

Under the oxidation reaction conditions, a modified nanocarbon-based material is used as a catalyst to react sulfide and peroxide in contact with each other in a slurry bed reactor to improve the utilization rate of peroxide and the selectivity of sulfoxide.

Benefits of technology

Through this method, the utilization rate of peroxide and the selectivity of sulfoxide are improved, and the production cost of dimethyl sulfoxide is reduced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a method for oxidizing sulfide, which comprises: under the condition of oxidation reaction, sulfide and peroxide are contacted and reacted in a slurry bed reactor in the presence of a catalyst, the catalyst contains a modified nano carbon-based material, and a heat extraction device is arranged in the slurry bed reactor; the preparation steps of the modified nano carbon-based material are as follows: a polysaccharide compound and an inorganic base are mixed and then subjected to hydrothermal treatment, and the obtained reactant is dried. The method of the present invention has high selectivity of sulfoxide and high utilization rate of peroxide, and can reduce the operation cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for oxidizing thioether. Background Art

[0002] Dimethyl sulfoxide (DMSO) is a sulfur-containing organic compound and a highly polar inert solvent. It is widely used as a solvent and reaction reagent. In addition, dimethyl sulfoxide has a high selective extraction ability and can be used as an extraction solvent for separating alkanes and aromatic hydrocarbons. At the same time, in the pharmaceutical industry, dimethyl sulfoxide can not only be directly used as a raw material and carrier for certain drugs, but is also often added to drugs as an active ingredient in analgesics.

[0003] Dimethyl sulfoxide generally adopts dimethyl sulfide oxidation method to prepare, and according to the difference of used oxidant and oxidation mode, generally comprises nitric acid oxidation method, peroxide oxidation method, ozone oxidation method, anodic oxidation method and nitrogen dioxide oxidation method.Wherein the reaction conditions of peroxide oxidation method are gentle, equipment and process route are simple, product does not need alkali to neutralize, and is basically pollution-free to environment.But, in peroxide oxidation method, the price of oxidant is high and consumption is large, has increased the production cost of dimethyl sulfoxide, has limited the scope of application of peroxide oxidation method.Therefore, how to improve the effective utilization rate of oxidant, reduce the production cost of dimethyl sulfoxide is an important topic. Summary of the invention

[0004] In order to achieve the above object, the present invention provides a method for oxidizing thioether, which has high selectivity for the target product and high utilization rate of peroxide.

[0005] The present invention provides a method for oxidizing sulfide, which comprises: under oxidation reaction conditions, allowing sulfide and peroxide to contact and react in a slurry bed reactor in the presence of a catalyst, wherein the catalyst contains a modified nano-carbon-based material, and a heat extraction device is arranged in the slurry bed reactor;

[0006] The preparation steps of the modified nano carbon-based material are as follows: a polysaccharide compound and an inorganic base are mixed and then subjected to hydrothermal treatment, and the obtained reactant is dried.

[0007] Optionally, the particle size of the catalyst is 5 to 500 nm, preferably 20 to 250 nm.

[0008] Optionally, the surface carbon content of the modified nano-carbon-based material is 50-95% by weight, the oxygen content is 5-50% by weight, and the hydrogen content is 0-5% by weight;

[0009] Preferably, the content of carbon is 70-90% by weight, the content of oxygen is 10-30% by weight, and the content of hydrogen is 0.1-1% by weight.

[0010] Optionally, the molar ratio of the thioether to the peroxide is 1:(0.1-2), preferably 1:(0.5-1.5).

[0011] Optionally, the thioether is selected from dimethyl sulfide, anisole, methyl ethyl sulfide, diethyl sulfide or thiophene;

[0012] The peroxide is one or more selected from hydrogen peroxide, tert-butyl hydroperoxide, cumene peroxide, cyclohexyl hydroperoxide, peracetic acid and peroxypropionic acid;

[0013] The polysaccharide compound is selected from one or more of cellulose, starch, hemicellulose, chitin, hyaluronic acid, chondroitin sulfate and agar;

[0014] The inorganic base is selected from one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, barium hydroxide, lithium hydroxide and ammonia water.

[0015] Optionally, the conditions of the hydrothermal treatment include: a temperature of 180-420° C. and a time of 6-48 hours.

[0016] Optionally, the weight ratio of the polysaccharide compound to the inorganic base is 1:(0.01-50), preferably 1:(0.1-5).

[0017] Optionally, the oxidation reaction conditions include: temperature of 0-80°C; pressure of 0-3MPa in gauge pressure.

[0018] Optionally, the drying may be freeze drying or constant temperature drying, preferably freeze drying;

[0019] The freeze-drying conditions include: temperature of -45°C to -5°C, time of 1 to 96 hours, and vacuum degree of 5 to 180 Pa.

[0020] Optionally, the method comprises: contacting and reacting the thioether and the peroxide in the presence of the catalyst and the solvent;

[0021] The weight ratio of the thioether to the solvent is 1:(0.1-20);

[0022] The solvent is selected from organic solvents and / or inorganic solvents;

[0023] The organic solvent is selected from C 1 -C 6 Alcohol, C 3 -C 8 Ketone and C 2 -C 6 One or more of the nitriles; the inorganic solvent is deionized water.

[0024] Through the technical scheme, the method of the present invention has high selectivity for sulfoxide and high utilization rate of peroxide, and can reduce operating costs.

[0025] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION

[0026] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0027] The present invention provides a method for oxidizing sulfide, which comprises: under oxidation reaction conditions, allowing sulfide and peroxide to contact and react in a slurry bed reactor in the presence of a catalyst, wherein the catalyst contains a modified nano-carbon-based material, and a heat extraction device is arranged in the slurry bed reactor;

[0028] The preparation steps of the modified nano carbon-based material are as follows: a polysaccharide compound and an inorganic base are mixed and then subjected to hydrothermal treatment, and the obtained reactant is dried.

[0029] The method of the invention can effectively improve the utilization rate of peroxide, improve the selectivity of sulfoxide and reduce the operation cost.

[0030] According to the present invention, the heat extraction device is any device known to those skilled in the art that can extract reaction heat from a reaction system, such as a heat extraction coil, to effectively remove reaction heat, thereby further improving the utilization rate of peroxide.

[0031] According to the present invention, the particle size of the catalyst can vary within a relatively large range, for example, it can be 5 to 500 nm, preferably 20 to 250 nm. Particle size refers to the maximum three-dimensional length of the particle, that is, the distance between two points on the particle with the largest distance. Particle size can be measured using a transmission electron microscope, and the measurement conditions and methods can be conventionally used by those skilled in the art, which will not be described in detail here. The catalyst of the present invention has a particle size of suitable size, which is conducive to promoting the oxidation reaction of thioether, and further improving the selectivity of sulfoxide and the utilization rate of peroxide.

[0032] According to the present invention, the content of surface carbon element of the modified nano carbon-based material can be 50-95% by weight, preferably 70-90% by weight, the content of oxygen element can be 5-50% by weight, preferably 10-30% by weight, and the content of hydrogen element can be 0-5% by weight, preferably 0.1-1% by weight. The content of surface carbon element, oxygen element and hydrogen element of the modified nano carbon-based material refers to the content of carbon element, oxygen element and hydrogen element obtained by analyzing and measuring the modified nano carbon-based material by the XPS method. The specific analysis method of XPS is well known to those skilled in the art and will not be repeated here.

[0033] According to the present invention, the molar ratio of the thioether to the peroxide can vary within a wide range, for example, it can be 1:(0.1-2), preferably 1:(0.5-1.5). The molar ratio of the thioether to the peroxide is suitable within the above range, which can further improve the selectivity of the reaction product.

[0034] According to the present invention, the thioether is selected from dimethyl sulfide, anisyl thioether, methyl ethyl sulfide, diethyl sulfide or thiophene.

[0035] According to the present invention, peroxide refers to a compound containing -OO-bonds in the molecular structure, which can be selected from hydrogen peroxide, hydroperoxide and peracid. The hydroperoxide refers to a substance obtained by replacing a hydrogen atom in a hydrogen peroxide molecule with an organic group. The peracid refers to an organic oxygen-containing acid containing -OO-bonds in the molecular structure. Specific examples of the peroxide may include but are not limited to one or more of hydrogen peroxide, tert-butyl hydroperoxide, isopropylbenzene peroxide, cyclohexyl hydroperoxide, peracetic acid and peroxypropionic acid, preferably hydrogen peroxide, and the specific existence form of hydrogen peroxide is not limited, and can be in any form. In a preferred embodiment of the present invention, hydrogen peroxide exists in the form of an aqueous solution to improve the safety of the reaction. The content of hydrogen peroxide in the aqueous hydrogen peroxide solution can vary in a large range, for example, it can be 20-80% by weight. The aqueous hydrogen peroxide solution of the above concentration can be prepared by conventional methods or can be commercially available.

[0036] According to the present invention, the polysaccharide compound is selected from one or more of cellulose, starch, hemicellulose, chitin (chitin), hyaluronic acid, chondroitin sulfate and agar, etc.; the inorganic base is selected from one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, barium hydroxide, lithium hydroxide and ammonia water. There is no specific restriction on the concentration of the inorganic base, which can be selected according to actual needs, for example, it can be 0.1-40% by weight.

[0037] According to the present invention, the hydrothermal treatment is well known to those skilled in the art and can be carried out in a heat-resistant sealed reactor. The conditions of the hydrothermal treatment may include: a temperature of 120-420° C. for 1-48 hours, preferably a temperature of 180-350° C. for 2-24 hours. There is no specific limitation on the pressure, for example, it can be carried out under applied pressure or autogenous pressure.

[0038] According to the present invention, the weight ratio of the polysaccharide compound to the inorganic base can be varied in a wide range. In a specific embodiment, the weight ratio of the polysaccharide compound to the inorganic base can be 1:(0.01-50), preferably 1:(0.1-5). Within the above range, a catalyst having good catalytic performance for thioether can be prepared, which is beneficial to further improve the selectivity of sulfoxide and the effective utilization rate of peroxide.

[0039] According to the present invention, the oxidation reaction conditions may include: a temperature of 0-80°C, preferably 30-50°C; a pressure of 0-3MPa, preferably 0.1-2.5MPa, as a gauge pressure. The oxidation reaction of thioether can be carried out in equipment well known to those skilled in the art. In a specific embodiment, the oxidation reaction is carried out in a slurry bed reactor. Preferably, a heat extraction coil for heat exchange and stirring is also provided in the slurry bed reactor to make the reaction more uniform and sufficient, and the heat exchange and stirring functions can be integrated into the reactor, which is conducive to saving space in the reactor, increasing the processing capacity of the reaction device per unit time, and improving the reaction efficiency. The stirring rate of the heat extraction plate can be adjusted according to the reaction needs. Preferably, the stirring rate is 20-1000rpm.

[0040] According to the present invention, there is no limitation on the specific method of drying, which can be conventionally adopted by technicians in the field. Examples of drying can include but are not limited to freeze drying or constant temperature drying, preferably freeze drying; freeze drying conditions can include: temperature of -45°C to -5°C, time of 1 to 96 hours, vacuum degree of 5 to 180 Pa, preferably, temperature of -40°C to -8°C, time of 5 to 70 hours, vacuum degree of 15 to 160 Pa.

[0041] According to the present invention, the method comprises: allowing thioether and peroxide to contact and react in the presence of a catalyst and a solvent; the solvent can be any liquid substance that can dissolve thioether and peroxide or promote the mixing of the two and promote the dissolution of dimethyl sulfoxide. The solvent is selected from organic solvents and / or inorganic solvents; the organic solvent is selected from C 1 -C 6 Alcohol, C 3 -C 8 Ketone and C 2 -C 6The inorganic solvent is deionized water. Specific examples of the solvent may include, but are not limited to, water, methanol, ethanol, n-propanol, isopropanol, tert-butanol, isobutanol, acetone, butanone and acetonitrile. Preferably, the solvent is selected from water and C 1 -C 6 More preferably, the solvent is methanol and / or water. The present invention does not impose any specific restrictions on the amount of the solvent, as long as the thioether and the peroxide can be fully mixed. In a specific embodiment, the weight ratio of the thioether to the solvent can be 1: (0.1-20), more preferably 1: (1-10).

[0042] According to the present invention, after the oxidation reaction is completed, the reaction product is taken out. The method for taking out the reaction product is not specifically limited. For example, the mixture after the oxidation reaction can be fractionated to obtain the reaction product. The conditions for fractionation are well known to those skilled in the art and will not be described in detail herein.

[0043] The present invention is further illustrated by the following examples, but the present invention is not limited thereto.

[0044] In the following examples and comparative examples, unless otherwise specified, all reagents used were commercially available analytically pure reagents, wherein the peroxide used was 30 wt % hydrogen peroxide solution.

[0045] XPS was used to analyze the carbon content, oxygen content and hydrogen content on the surface of the modified nanocarbon-based material.

[0046] In the following examples and comparative examples, gas chromatography was used to analyze the content of each component in the obtained reaction product, and on this basis, the following formulas were used to calculate the dimethyl sulfide conversion rate, the effective utilization rate of peroxide, and the dimethyl sulfoxide selectivity:

[0047] Conversion rate of dimethyl sulfide (X 硫醚 ) = [(molar amount of dimethyl sulfide added - molar amount of unreacted dimethyl sulfide) / molar amount of dimethyl sulfide added] × 100%;

[0048] Peroxide effective utilization rate (U 氧化剂 ) = [molar amount of dimethyl sulfoxide generated by the reaction / (molar amount of peroxide added - molar amount of unreacted peroxide)] × 100%;

[0049] Dimethyl sulfoxide selectivity (S 亚砜 ) = [the molar amount of dimethyl sulfoxide produced by the reaction / (the molar amount of dimethyl sulfide added-the molar amount of unreacted dimethyl sulfide)] × 100%.

[0050] Preparation Example 1

[0051] 10 g of starch was added into 50 mL of 2 wt % ammonia solution, sealed in a high-pressure reactor and subjected to hydrothermal reaction at 200° C. under autogenous pressure for 12 h. After being taken out, it was freeze-dried at -25° C. and 100 Pa for 4 hours to obtain the modified nano-carbon-based material A used in the present invention (the average particle size of the modified nano-carbon-based material is 68 nm, and its carbon content is 89.4 wt %, oxygen content is 10.3 wt %, and hydrogen content is 0.3 wt %).

[0052] Preparation Example 2

[0053] 5 g of agar was added to 30 mL of 1 wt % sodium hydroxide aqueous solution, and the mixture was sealed in a high-pressure reactor for hydrothermal reaction at 250° C. under autogenous pressure for 6 h. After being taken out, the mixture was freeze-dried at -25° C. and 100 Pa for 4 hours to obtain a modified nano-carbon-based material B used in the present invention (the average particle size of the modified nano-carbon-based material was 16 nm, and the carbon content was 69.2% by weight, the oxygen content was 27.7% by weight, and the hydrogen content was 3.1% by weight).

[0054] Preparation Example 3

[0055] 15 g of hydroxymethyl cellulose was added into 80 mL of 10 wt % sodium hydroxide aqueous solution, sealed into a high-pressure reactor and subjected to hydrothermal reaction at 350° C. autogenous pressure for 18 h. After being taken out, it was freeze-dried at -25° C. and 100 Pa for 4 hours to obtain the modified nano-carbon-based material C used in the present invention (the average particle size of the modified nano-carbon-based material is 35 nm, and its carbon content is 81.5 wt %, oxygen content is 18.0 wt %, and hydrogen content is 0.5 wt %).

[0056] Preparation Example 4

[0057] 5 g of agar was added to 25 mL of 1 wt % sodium hydroxide aqueous solution, and the mixture was sealed in a high-pressure reactor and subjected to hydrothermal reaction at 150° C. autogenous pressure for 12 h. The mixture was taken out and freeze-dried at -25° C. and 100 Pa for 4 hours to obtain a modified nano-carbon-based material D used in the present invention (the average particle size of the modified nano-carbon-based material was 20.2 nm, and the carbon content was 45.8% by weight, the oxygen content was 50.2% by weight, and the hydrogen content was 4.0% by weight).

[0058] Preparation Example 5

[0059] The modified nanocarbon-based material E was prepared by the same method as in Preparation Example 1, except that the temperature of the hydrothermal reaction was 400°C and the time was 1 hour (the average particle size of the modified nanocarbon-based material was 19 nm, and its carbon content was 80.1% by weight, its oxygen content was 15.9% by weight, and its hydrogen content was 4.0% by weight).

[0060] Example 1

[0061] First, liquid dimethyl sulfide, hydrogen peroxide and methanol are added together into a slurry bed reactor equipped with a heat extraction coil to contact with the modified nanocarbon-based material A to obtain a mixture containing sulfoxide, wherein the heat extraction coil in the reactor has a stirring function. Among them, the molar ratio of dimethyl sulfide to hydrogen peroxide is 1:1, and the weight ratio of dimethyl sulfide to methanol is 1:4; the reaction temperature is 30°C, the stirring rate of the heat extraction coil is 120rpm, and the pressure is 0.8MPa. The reaction mixture obtained after the reaction is carried out for 2 hours is subjected to gas chromatography analysis, and the conversion rate of dimethyl sulfide, the effective utilization rate of hydrogen peroxide and the selectivity of dimethyl sulfoxide are calculated. The results are listed in Table 1.

[0062] Example 2

[0063] The sulfide was oxidized by the same method as in Example 1, except that the modified nano-carbon-based material used was modified nano-carbon-based material B.

[0064] Example 3

[0065] The sulfide was oxidized in the same manner as in Example 1, except that no solvent was added and other conditions were the same.

[0066] Example 4

[0067] The sulfide was oxidized by the same method as in Example 2, except that no solvent was added and other conditions were the same.

[0068] Example 5

[0069] The sulfide was oxidized by the same method as in Example 1, except that the modified nano-carbon-based material used was modified nano-carbon-based material C.

[0070] Example 6

[0071] The sulfide was oxidized by the same method as in Example 1, except that the modified nano-carbon-based material used was modified nano-carbon-based material D.

[0072] Example 7

[0073] The sulfide was oxidized by the same method as in Example 1, except that the modified nano-carbon-based material used was modified nano-carbon-based material E.

[0074] Comparative Example 1

[0075] The sulfide was oxidized by the same method as in Example 1, except that the catalyst was untreated starch.

[0076] Comparative Example 2

[0077] The sulfide was oxidized using the same method as in Example 2, except that the catalyst was untreated agar.

[0078] Table 1

[0079] serial number <![CDATA[X 硫醚 (%)]]> <![CDATA[U 氧化剂 (%)]]> <![CDATA[S 亚砜 (%)]]> Example 1 65.6 84 96 Example 2 59.1 83 94 Example 3 57.9 80 92 Example 4 55.7 82 91 Example 5 63.4 85 95 Example 6 54.0 81 93 Example 7 61.8 80 90 Comparative Example 1 41.3 73 88 Comparative Example 2 33.5 70 90

[0080] The method of the invention has high selectivity for preparing the target product sulfoxide within a preferred range and high effective utilization rate of peroxide.

[0081] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0082] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0083] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for oxidizing thioether, the method comprising: Under oxidation reaction conditions, sulfide and peroxide are contacted and reacted in a slurry bed reactor in the presence of a catalyst, wherein the catalyst contains a modified nano-carbon-based material, and a heat extraction device is provided in the slurry bed reactor; The preparation steps of the modified nano-carbon-based material are as follows: mixing a polysaccharide compound and an inorganic base, performing a hydrothermal treatment, and drying the obtained reactant; The conditions of the hydrothermal treatment include: a temperature of 150-420°C; The weight ratio of the polysaccharide compound to the inorganic base is 1: (0.01-50); the polysaccharide compound is selected from one or more of cellulose, starch, hemicellulose, chitin, hyaluronic acid, chondroitin sulfate and agar.

2. The method according to claim 1, wherein: The particle size of the catalyst is 5-500 nm.

3. The method according to claim 2, wherein: The particle size of the catalyst is 20-250 nm.

4. The method according to claim 1, wherein: The surface carbon content of the modified nano-carbon-based material is 50-95% by weight, the oxygen content is 5-50% by weight, and the hydrogen content is 0-5% by weight.

5. The method according to claim 4, wherein: The surface carbon content of the modified nano-carbon-based material is 70-90% by weight, the oxygen content is 10-30% by weight, and the hydrogen content is 0.1-1% by weight.

6. The method according to claim 1, wherein: The molar ratio of the thioether to the peroxide is 1:(0.1-2).

7. The method according to claim 6, wherein: The molar ratio of the thioether to the peroxide is 1:(0.5-1.5).

8. The method according to claim 1, wherein: The thioether is selected from dimethyl sulfide, anisole, methyl ethyl sulfide, diethyl sulfide or thiophene; The peroxide is one or more selected from hydrogen peroxide, tert-butyl hydroperoxide, cumene peroxide, cyclohexyl hydroperoxide, peracetic acid and peroxypropionic acid; The inorganic base is selected from one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, barium hydroxide, lithium hydroxide and ammonia water.

9. The method according to claim 1, wherein: The conditions of the hydrothermal treatment include: a temperature of 180-420° C. and a time of 6-48 hours.

10. The method according to claim 1, wherein: The weight ratio of the polysaccharide compound to the inorganic base is 1:(0.1-5).

11. The method according to claim 1, wherein: The oxidation reaction conditions include: temperature of 0-80°C; pressure of 0-3MPa in gauge pressure.

12. The method according to claim 1, wherein: The drying can be freeze drying or constant temperature drying.

13. The method according to claim 1, wherein: The drying is freeze drying; the freeze drying conditions include: temperature of -45°C to -5°C, time of 1 to 96 hours, and vacuum degree of 5 to 180Pa.

14. The method according to claim 1, wherein: The method comprises: contacting and reacting the thioether and the peroxide in the presence of the catalyst and the solvent; The weight ratio of the thioether to the solvent is 1:(0.1-20); The solvent is selected from organic solvents and / or inorganic solvents; The organic solvent is selected from one or more of C1-C6 alcohols, C3-C8 ketones and C2-C6 nitriles; and the inorganic solvent is deionized water.

Citation Information

Patent Citations

  • Method of oxidizing thioether

    CN111763161A